Insuficiência Cardíaca com Fração de Ejeção Intermédia - Estado da Arte - Helena Margarida Teixeira Ferreira (2020)
In 2016, the European Society of Cardiology guidelines introduced a new group in the classification of patients with Heart Failure - Heart Failure with Mid-range ejection fraction- corresponding to patients with Left-Ventricular Ejection Fraction (LVEF) between 40% and 49%. The creation of this new category, intermediate to the two pre-existing groups, Heart Failure with Reduced Ejection Fraction (HFrEF) and Heart Failure with Preserved Ejection Fraction (HFpEF), intended to promote the investigation of this group which represents up to 25% of patients with Heart Failure. In this review we aim to summarize the current evidence on HFmrEF and discuss this distinction. Generally, patients with HFmrEF have clinical characteristics intermediate between the mentioned two pre-existing groups. Ischemic heart disease appears as the characteristic where these patients are more similar to patients with HFrEF. In terms of prognosis and response to treatment, HFmrEF seems to be more similar to HFrEF, suggesting that etiology may be more important than LVEF for stratification. Some studies have shown benefits in the use of drugs currently recommended for patients with HFrEF in patients with HFmrEF. Additional research is needed, not only to better characterize this group of patients, but also to understand which are the best therapeutic strategies.